2007
DOI: 10.1186/1477-7525-5-65
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of child and adolescent retinoblastoma survivors in the Netherlands

Abstract: Background: To assess health-related quality of life (HRQoL) in children (8-11 years) and adolescents (12-18 years) who survived retinoblastoma (RB), by means of the KIDSCREEN self-report questionnaire and the proxy-report version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
97
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 27 publications
(25 reference statements)
7
97
0
4
Order By: Relevance
“…For example, 111/122 (91%) underwent enucleation and 27/122 (22%) patients received radiation therapy in our study, compared with 60% and 15% in the Dutch study, respectively. [12] This may be responsible for worse overall QOL in our population as compared with their siblings, whereas no differences in QOL were noted in the Dutch study when comparing the survivors with the Dutch reference groups. [12] Another notable difference was the control population wherein we used the siblings in our study, whereas the Dutch study used the reference Dutch population.…”
Section: Discussionmentioning
confidence: 70%
“…For example, 111/122 (91%) underwent enucleation and 27/122 (22%) patients received radiation therapy in our study, compared with 60% and 15% in the Dutch study, respectively. [12] This may be responsible for worse overall QOL in our population as compared with their siblings, whereas no differences in QOL were noted in the Dutch study when comparing the survivors with the Dutch reference groups. [12] Another notable difference was the control population wherein we used the siblings in our study, whereas the Dutch study used the reference Dutch population.…”
Section: Discussionmentioning
confidence: 70%
“…The 40% eye salvage rate in the Dutch study samples might be the reason why the quality of life of Dutch pediatric patients with RB was close to that of normal children. 11,13 The differences in scores of the social and school dimensions in the PedsQL TM 4.0 between pediatric patients with RB and the control group were statistically significant. The differences in scores of these dimensions among Dutch pediatric patients with RB were not statistically significant, and only pediatric patients in the 12-18-yearold age range had certain difficulties in "peer relationship and social support."…”
Section: Discussionmentioning
confidence: 97%
“…The differences in scores of these dimensions among Dutch pediatric patients with RB were not statistically significant, and only pediatric patients in the 12-18-yearold age range had certain difficulties in "peer relationship and social support." 11 Weintraub et al reported that Israeli pediatric patients with RB were affected by the disease and their daily activities were restricted, thus causing absences from schools and reductions in participation in all types of activities, which significantly affected the children's scores in the school dimension. 12 An Indian study reported that because of differences in the medical and social support systems of pediatric patients with RB from those in Western societies, the differences in scores of the social and school dimensions between pediatric patients and the control group were statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups, on the other hand, propose IACT for all eyes that not need urgent enucleation (Gobin et al 2011;Abramson et al 2012) based on its lower toxicity compared with systemic chemotherapy, even for those unilaterally affected with poor potential vision. However, considering that many patients and their families feel that enucleation affects behavioural adjustment (van Dijk et al 2007), avoiding enucleation may be not only important from a cosmetic standpoint but may possibly provide better quality of life in some cases. In our limited study population, this approach proved safe and effective when performed following prospectively defined guidelines for patient eligibility.…”
Section: Discussionmentioning
confidence: 99%